Effects of high light exposure and heterologous expression of β-carotene ketolase on the metabolism of carotenoids in Chlamydomonas reinhardtii - Mei, Rui; Yang, Haihong; Guo, Chunli; Hong, Zeyu; Hu, Zhangli; Wu, Yan; Huang, Danqiong; Wang, Chaogang (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionStress from high light exposure and overexpression of β-carotene ketolase can have significant effects on the synthesis of carotenoids in Chlamydomonas reinhardtii. As a promising platform for carotenoid production, C. reinhardtii needs further research and technological innovation to address challenges, such as environmental interference, exogenous gene expression, and metabolic regulation, to achieve efficient and sustainable production of carotenoids.MethodsAppropriate β-carotene ketolase were selected from different organisms and subjected for codon optimization based on the preferences of the nuclear genome of C. reinhardtii. After designation, including intron insertion and chloroplast transit peptide, expression vectors were constructed and used for nuclear transformation of C. reinhardtii CC849 by bead milling method. Subsequently, DNA-PCR and RT-PCR were used to identify positive transformants grown with antibiotic stress, LC-MS/MS and metabolic analysis were performed to evaluate the products of transformants.ResultsIn this study, carotenoid metabolism regulation in C. reinhardtii was investigated in a time-dependent manner through high light exposure and heterologous expression of β-carotene ketolase. The results suggested that the stress from high light exposure (500 μmol/m2/s) negatively regulated the accumulation of β-carotene; positively induced the accumulation of zeaxanthin, echinenone, and canthaxanthin; and continuously promoted accumulation of zeaxanthin and canthaxanthin in C. reinhardtii. Metabolomics analysis suggested that high light exposure stress promoted biosynthesis of carotenoids, improved the intermediates associated with the astaxanthin synthesis pathway, and promoted conversion of β-carotene to downstream substances. Several strategies were implemented to improve canthaxanthin production in C. reinhardtii to achieve overexpression of β-carotene ketolase genes from different sources, including strong promoters, insertion introns, and chloroplast conduction peptides. It was found that β-carotene, echinenone, and canthaxanthin were all significantly increased in the transformed C. reinhardtii overexpressing β-carotene ketolase. Among these, the highest canthaxanthin content was found in pH124-CrtO, which was seven times that observed in the wild type. Moreover, the metabolomics analysis of carotenoids showed promotion of the abscisic acid and astaxanthin pathways in the transformed C. reinhardtii.DiscussionThe results of this study provide a new scheme for manipulating the metabolism of carotenoids and promoting the synthesis of high-value carotenoids in C. reinhardtii.